THE ESSENCE AND LEGAL SIGNIFICANCE OF JUDICIAL ACTS OF THE ADMINISTRATIVE COURT - Avetisyan, Karen (State and Law, 2021)
This article is devoted to the identification of the essence and legal significance of judicial acts adopted by the administrative court in the direction of solving administrative and legal issues arising from public legal relations taking as a basis also the specific division of these acts (resolving the case on the merits and interim judicial acts). The author, in particular, formulated the belief that, among other interim judicial acts issued by the administrative court, and, as a rule, the legal significance of judicial acts that resolve a case on the merits is reduced to identifying violations of the rights of individuals or legal entities and forming the necessary behavior of the relevant authorities to exclude these violations. At the same time, within the framework of the article, the author emphasized that in certain cases, judicial acts of the administrative court, being individual legal acts, also have the character of a negative normative legal act. In particular, emphasizing that judicial acts adopted by the administrative court (which entered into legal force) as a result of the proceedings to verify the legality of normative legal acts in cases subject to the administrative court, actually make changes to the system of existing legal norms the author expressed confidence that in this sense, the judicial acts indicated in their legal force are equal to the law. As a result of the analysis carried out by the article, the author came to the conclusion that the essence and legal meaning of the acts of the administrative court should be based on the specific meaning of these acts stating that it would be correct to fix the general and special characteristics of the essence and meaning of judicial acts of the administrative court.